Importance of naturalized breeds as a base for the formation of exotic sheep (Ovis aries) breeds in tropical altitude regions - Joyce Azambuja de Oliveira; Andrea Alves do Egito; Bruno do Amaral Crispim; Fernando Miranda de Vargas Junior; Leonardo de Oliveira Seno; Alexeia Barufatti (Genetics and Molecular Biology)
Abstract Recent molecular tools and technologies have marked the discovery of the origin and domestication processes of a wide variety of species, using either genomic or mitochondrial molecular markers to provide input for selection programs, as well as the management and conservation of animal breeds. This study aimed to analyze genes of mitochondrial DNA of the following sheep (Ovis aries) breeds: Pantaneira, Bergamácia, Dorper, White Dorper, Ile de France and Hampshire Down, to obtain their population genetic parameters and investigate the origin of these sheep populations reared in the State of Mato Grosso do Sul. The analysis of mitochondrial DNA allowed to infer their phylogenetic relationships and revealed significant differences among them when compared with each other and with sequences obtained from GenBank. Through the formation of haplotypes, it was noted that the Pantaneira breed served as the maternal basis for the formation of the other breeds reared in the region, and it was possible to suggest a European origin for the sheep populations studied.